2021
DOI: 10.1186/s12885-021-08994-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lung cancer measures of the National Cancer Network pilot study in Poland for potential improvement in the quality of advanced-stage lung cancer therapy

Abstract: Background This study aimed to present the performance of the National Cancer Network’s (NCN) pilot program in the Lower Silesian Voivodeship (southwestern province of Poland with a population of 2,9 million in 2019), to analyse measures describing lung cancer patients and to determine whether those measures can be used to improve the treatment outcomes of stage III and IV patients with lung cancer in Poland. Methods Three measures of the NCN pilot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
0
1
Order By: Relevance
“…It is worth referring to an analysis of tests performed for genetic and molecular predictors in patients at clinical stages 3 and 4 and the epidemiological structure of this group of patients. Compared to the findings presented in that analysis, which cover the NCN’s period of functioning between 2019 and 2020 in Lower Silesia Province, the current study showed no significant differences in the scope of the analysed aspects [ 20 ]. Only the percentage of stage 3 patients who underwent an assessment of predictors decreased, from 40% at the end of 2020 to 35% at the end of 2021.…”
Section: Discussioncontrasting
confidence: 86%
“…It is worth referring to an analysis of tests performed for genetic and molecular predictors in patients at clinical stages 3 and 4 and the epidemiological structure of this group of patients. Compared to the findings presented in that analysis, which cover the NCN’s period of functioning between 2019 and 2020 in Lower Silesia Province, the current study showed no significant differences in the scope of the analysed aspects [ 20 ]. Only the percentage of stage 3 patients who underwent an assessment of predictors decreased, from 40% at the end of 2020 to 35% at the end of 2021.…”
Section: Discussioncontrasting
confidence: 86%